: A NOVEL TECHNIQUE OF REAL TIME VIDEO MONITORING SYSTEM (International Journal of Engineering and Computer Science, 2013)
The project entitled “A Novel Technique of Real Time Video Monitoring System” has been developed using JAVA as front end. The main objective of this project is to implement video monitoring in the international banking domain in order to make in the banks in a security way. This project uses five powerful modules namely user interface design, video capture, frame grabber, image comparison and frame into video. The goal of user interface design is to make the user’s interaction as simple and efficient as possible.  Video capturing is technology of electronically capturing, processing, storing, transmitting and reconstructing a sequence of still images representing scenes in motion. This is a digital image taken by the host operating systems or software running on the computer, but it can also be a capture made by a camera or a device intercepting the video output of the display. Existing system records all the transaction of a particular day or a session. User can find theft only from location monitoring full video records. This is a long process. In the proposed system recording starting only when changes take places as compared to the original images. The recording stops or does not take place when the original image is present